Observations of condensation nuclei in the 1987 airborne Antarctic ozone experiment - Smith, S. D.; Ferry, G. V.; Loewenstein, M.; Wilson, J. C. (1988)
The condensation nucleus counter (CNC) flown of the NASA ER-2 in the Airborne Antarctic Ozone Experiment provides a measurement of the number mixing ratio of particles which can be grown by exposure to supersaturated n-butyl alcohol vapor to diameters of a few microns. Such particles are referred to as condensation nuclei (CN). The ER-2 CNC was calibrated with aerosols of known size and concentration and was found to provide an accurate measure of the number concentration of particles larger than about 0.02 micron. Since the number distribution of stratospheric aerosols is usually dominated by particles less than a few tenths of micron in diameter, the upper cutoff of the ER-2 CNC has not been determined experimentally. However, theory suggests that the sampling and counting efficiency should remain near one for particles as large as 1 micron in diameter. Thus, the CN mixing ratio is usually a good measure of the mixing ratio of submicron particles.